ANALISIS PENDAPATAN UNTUK MENINGKATKAN LABA BERSIH PADA KOPERASI PEGAWAI REPUBLIK INDONESIA TUTWURI DIKBUDMORA KOTA MADIUN - Danik Karyawati; Supriyatun; Eny Kusumawardhani; Mohamad Nur Efendi (JAMER : Jurnal Akuntansi Merdeka, 2024)
This research aims to determine the level of income growth and net profit growth, and whether the increase in income each year is always followed by income growth in the following year. Likewise, whether the increase in net profit each year is followed by growth in net profit in the following year. The research object is KPRI Dikbudmudora which is located in the city of Madiun. Using Income data, Operational data, and Tax data from KPRI Dikbudmudora Madiun city from 2019 to 2021. The data analysis technique uses descriptive analysis techniques. The data collection technique used is documentation. The results of this research show that the income and net profit at KPRI Dikbudmudora, Madiun City in 2019-2020 has increased every year, however, the level of efficiency in the company's operational expenses has decreased, so this is one of the factors causing the growth rate of income and net profit. The company's net income fluctuates every year.